PENGARUH PEMERIKSAAN DAN PELAKSANAAN SELF ASSESMENT SYSTEM TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK BADAN PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA BANDA ACEH - Cut Delsie Hasrina; Yusri Yusri; Nona Maulina (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
The purpose of this research is to determine the effect of examination and implementation of self assessment system on the level of compliance with corporate tax payers registered in Taxes Service Office (KPP) Pratama Banda Aceh. The used data is in form of primary data by giving the questionnaire to the taxpayers. The sampling technique is random sampling. The sample of this study is 100 respondents, from 100 respondents, there are not all questionnaires did not return because there were 9 questionnaires were not returned, 7 questionnaires were incomplete and therefore unusable. The results showed that, inspection and implementation of self assessment system significantly influence taxpayer compliance rate on KPP Banda Aceh by testing simultaneously with the value of Fscore> Ftable and the value of Tscore> Ttable.